Hydrological responses to climate change in Mt. Elgon watersheds - Musau, John Mwanzia; Sang, J.; Gathenya, J.; Luedeling, Eike (Elsevier, 2015)
Study Region: The Upper catchments of the Nzoia River basin in western Kenya. Study Focus: The potential streamflow responses to climate change in the upper Nzoia River basin are studied. The Soil and Water Assessment Tool(SWAT) was forced withmonthly temperature and precipitation change scenarios for the periods 2011–2040 (2020s), 2041–2070 (2050s) and 2071–2100 (2080s). Data from 10 climate models and three greenhouse gases emission scenarios was downscaled using the delta change method and used in the SWAT model. Streamflow data for the periods 1986–1998 and 1973–1985 was used for model calibration and validation respectively. New Hydrological Insights for the Region: Comparison between the simulated baseline and future streamflow shows that in the Koitobos and Kimilili watersheds, August to December streamflow is likely to be highly altered. In the Kuywa watershed, March to June flows is likely to change considerably due to climate change. Major streamflow changes are likely in March to June and August to November in the Rongai watershed. Projected changes differed between the four watersheds despite their proximity, indicating different sensitivities to climate change and uncertainty about the potential hydrological impacts of climate change in the area.
Keywords: Climate change; Streamflow; Nzoia basin; Mt. Elgon; SWAT